2016
DOI: 10.1002/2015jf003732
|View full text |Cite
|
Sign up to set email alerts
|

A seismologically consistent expression for the total area and volume of earthquake‐triggered landsliding

Abstract: We present a new, seismologically consistent expression for the total area and volume of populations of earthquake-triggered landslides. This model builds on a set of scaling relationships between key parameters, such as landslide spatial density, seismic ground acceleration, fault length, earthquake source depth, and seismic moment. To assess the model we have assembled and normalized a catalog of landslide inventories for 40 shallow, continental earthquakes. Low landscape steepness causes systematic overpred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
214
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(220 citation statements)
references
References 124 publications
(243 reference statements)
5
214
1
Order By: Relevance
“…Below this threshold, landsliding is rare or minor, and therefore a reasonable estimation of the size and shape of the landslide distribution area could be found by intersecting the region where the peak ground acceleration exceeds a c and the region with sufficiently steep topography for landsliding to occur. Marc et al (2016b) have successfully modelled the total volume and area of the population of landslides due to a given earthquake, using seismological scaling laws to constrain the magnitude and extent of ground shaking. They assumed that a c is a threshold acceleration for damage above which an effective reduction of strength occurred within the hillslope materials, increasing the likelihood of failure of slopes steeper than the angle of internal friction and thus stable due to a significant cohesion.…”
Section: A Seismologically Consistent Expression For the Landslide DImentioning
confidence: 99%
See 3 more Smart Citations
“…Below this threshold, landsliding is rare or minor, and therefore a reasonable estimation of the size and shape of the landslide distribution area could be found by intersecting the region where the peak ground acceleration exceeds a c and the region with sufficiently steep topography for landsliding to occur. Marc et al (2016b) have successfully modelled the total volume and area of the population of landslides due to a given earthquake, using seismological scaling laws to constrain the magnitude and extent of ground shaking. They assumed that a c is a threshold acceleration for damage above which an effective reduction of strength occurred within the hillslope materials, increasing the likelihood of failure of slopes steeper than the angle of internal friction and thus stable due to a significant cohesion.…”
Section: A Seismologically Consistent Expression For the Landslide DImentioning
confidence: 99%
“…The mean depth of emission is assumed to be the mean asperity depth because asperities emit most of the high-frequency waves (Ruiz et al, 2011;Avouac et al, 2015) and seem to explain best the observed patterns and amounts of landsliding (Meunier et al, 2013b;Marc et al, 2016b). Note that waves with frequencies of 0.5 to 10 Hz are often the most important for landslide triggering because they have wavelengths ranging from the landslide size to the hillslope size (Marc et al, 2016b).…”
Section: A Seismologically Consistent Expression For the Landslide DImentioning
confidence: 99%
See 2 more Smart Citations
“…Within 48 h of the 25 April mainshock, initial estimates of the likely geographical distribution of landslides were based upon the outputs of the USGS ShakeMap and a limited number of reports from the ground (e.g., via social media). Although this provided a first-order approximation of potential landslide locations, coseismic landsliding is determined by the interactions between topography, ground shaking, and local site geology (Meunier et al, 2008;Parker et al, 2015;Marc et al, 2016). Empirical landslide susceptibility models (Gallen et al, 2016;Parker et al, 2017;Robinson et al, 2017) provided probabilistic estimates of the likelihood of a landslide at any point in space within the affected area.…”
Section: Chronology Of Rapid Landslide Assessment Using Optical Imagerymentioning
confidence: 99%